1985
DOI: 10.3168/jds.s0022-0302(85)81029-8
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Reproductive Performance of Dairy Cows

Abstract: We conducted two studies to determine how herd management practices and traits of individual cows affect performance of the herd and of the cow within a herd. Management practices, reproductive performance of the herd, and relationships between management and reproductive performance were characterized on 83 dairy farms with 7596 cows. Data included 21 management variables (e.g., facilities, herd health program, estrous detection program) and 8 performance variables obtained from Dairy Herd Improvement or unof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
52
3
2

Year Published

1990
1990
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(74 citation statements)
references
References 23 publications
17
52
3
2
Order By: Relevance
“…Han & Kim (2005) reported the intervals from calving to first service and conception were higher in the retained placenta group than in the control group, which is consistent with other reports (Ouweltjes et al, 1996). In some studies, however, the intervals from calving to first service and/or conception were not related to the occurrence of retained placenta (Coleman et al, 1985;Kaneko et al, 1997). RP increases the risk of fatty liver syndrome and ketosis (Han & Kim, 2005); the latter, in turn, delays the postpartum resumption of cyclic ovarian function and prolongs the interval from calving to f irst ovulation (Opsomer et al, 2000).…”
Section: Retained Placenta and Metritissupporting
confidence: 78%
See 1 more Smart Citation
“…Han & Kim (2005) reported the intervals from calving to first service and conception were higher in the retained placenta group than in the control group, which is consistent with other reports (Ouweltjes et al, 1996). In some studies, however, the intervals from calving to first service and/or conception were not related to the occurrence of retained placenta (Coleman et al, 1985;Kaneko et al, 1997). RP increases the risk of fatty liver syndrome and ketosis (Han & Kim, 2005); the latter, in turn, delays the postpartum resumption of cyclic ovarian function and prolongs the interval from calving to f irst ovulation (Opsomer et al, 2000).…”
Section: Retained Placenta and Metritissupporting
confidence: 78%
“…Hur et al (2011) concluded that there is a very close relationship between RP and postpartum diseases in dairy cattle after calving and RP increases risks for postpartum diseases such as metritis and mastitis, and culling hazards up to 60 DIM. Gaafar et al (2010) (Erb et al, 1981;Fourichon et al, 2000) and decrease milk yield (Coleman et al, 1985). Also, cows with severe metritis ate 2-6 kg dry matter less than healthy cows in the 2-3 weeks preceding the clinical signs of metritis (Huzzey et al, 2007), and to negatively affect reproductive performance (Opsomer et al, 2000;Melendez et al, 2004).…”
Section: Retained Placenta and Metritismentioning
confidence: 99%
“…Decrease in fertility is a major cause of economic loss with higher culling rate (Khatib et al, 2009). Prolonged interval (>85 days) between calving and onset of ovarian function is regarded as one of the most important reproductive problems (Coleman et al, 1985). Prolonged suppression due to negative feedback of progesterone secreted by the corpus luteum and the placenta during pregnancy causes the pituitary to be refractory at very early postpartum period (within 10-12 days) as indicated by lack of response to exogenous gonadotrophin-releasing hormone (Alam and Dobson, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…The economic losses associated with this problem are highly considerable resulted from increased veterinary expenses, insemination costs, reduced productivity, and losses due to involuntary culling. Reproductive problems have been the primary cause of culling in animal husbandry for many years (Coleman, 1985 and Opsomer et al, 2000).…”
Section: Introductionmentioning
confidence: 99%